Correlation of Social Media Metrics and Citations: A Case of Physical Review Letters - Gujjarappa, Nagaraja L; Chandrashekara, M. (Access: An International Journal of Nepal Library Association, 2023)
Scholarly literature is increasingly shared and discussed through the social web by researchers and academicians. The objective of the study is to investigate and measure the relationship of the citations with Altmetric Attention Score (AAS) for the selected articles in the physical review letter journal. Data extracted from Altmetric.com, Google Metrics, and from PlumXmetrics. Spearman correlation method was used to find the correlation between the Dimension and Scopus citations with AAS for selected articles, results show that the “p-value” stood as .009 and .002 which comes less than the significant level shows that high cited papers have a high AAS and the value of r stood as .772 and .851 which shows a high positive correlation between citations and AAS. US and Japan hold the top position countries with 816 and 326 tweets respectively. Mendeley and Twitter are contributing more to altmetrics scores. It is suggested that the Indian research community should also look forward to utilizing the social media platforms effectively to attract more audiences.